The bright side of the dark side: covert politics as an alternative to the negative impacts of coercive change - Lopes, M. E. (2011)
This study examines practitioners as individual actors by focusing on a general manager's individual account. With a two-week episode of political maneuvering as a starting point, the case shows how skilful strategizing on the part of the general manager is at the origin of significant organizational change. Specifically, the paper has three purposes. First, to offer insights to practitioners and scholars regarding how powerful managers purposefully seek to influence organizational context in a non-disclosed fashion. Second, to illustrate how single case microstudies open a route to understanding events that would otherwise be unattainable. The third, and most important, is to apply organizational politics concepts to characterize managerial covert political action in the implementation of a deliberate strategy. Specifically, emphasis is put on how contextual characteristics relate to political action. How they constrain and enable politics, and facilitate the use and maintenance of concealed motives.